Animal venoms in the production of medicines - Szabat, Przemysław Szabat; Poleszak, Julita; Szabat, Marta; Boreński, Grzegorz; Wójcik, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Toxicity of animal venom is a defense mechanism known to mankind for centuries for many species of animals. We are still learning the possibilities of its use as a substance with therapeutic potential, because on its basis several drugs known and commonly used in medicine were created. Aim of the study: To review research on the known and potential use of animal toxins as medicinal substances. Material and method: Standard criteria were used to review literature data. Search for articles in the PubMed database was carried out using the following keywords: animal venoms, medical use, snake venoms, drugs from venom, Description of the state of knowledge: Animal venoms have been used by man since ancient times. Due to many different mechanisms, they are able to modulate the tissue functions of the human body. In the form of already known drugs have an effect, among others. on the cardiovascular, nervous and circulatory systems. Research is also being carried out on their use in the treatment of other diseases such as autoimmune diseases and cancer. Summary: Due to the variety of substances in animal venom and their therapeutic properties, it is possible to use them for the production of medicines. However, many studies are needed to better understand them.